Características de historias de vida y patrones de abundancia relativa de Mugil curema Valenciennes, 1836 en la laguna de Pueblo Viejo, Veracruz - Torres Miranda, Claudia Iveth (Universidad Autónoma Metropolitana, 2012)
With the purpose of this work is getting information about distribution, abundance, age, growth and reproduction of lebrancha, Mullet curema, bimonthly samples were taken during one year in Lagoon of Pueblo Viejo, Veracruz, by making gatherings each two hours into 12 nictímeros cycles, All this into two different kinds of habitats, one of then was made with submerged vegetation (WSV) and the other without this kind of submerged vegetation (WOSV). During this study they were captured 1, 149 individuals. Specially a big amount individuals in the habitat WSV (P=0.035 was captured). The average size in the habitat WOSV (x =62.68 mm) was significantly bigger that in the habitat WSV (x =50.28), can be related to the fact that the habitat with vegetation represent protection areas and upbringing for young individuals. By analyzing the growth of the individuals in both habitats, it was found an interval of size from 19 to 221mm with model values between 22-28mm, 37-50mm and 90 mm been less common individuals with sizes bigger than 160 mm. For the age study were processed otoliths of 85 individuals, the structures were prepared and examined by different techniques but the evidence of the rings were not clearly observed . According to this observations and based on the size analysis showed by the individuals (in both habitats), 99.8% of the catched individuals were smaller or equal to 200mm of pattern longitude (LP), for which we can consider that most of the gathered individuals are less than a year of life. Seasonally, abundance showed an important pulse of recruitment on January (P=0.003), which was dominated by small individuals, this implies that during this month, exists an important pulse of recruitment. According to the method applied by ELEFAN I program, we could see such cohort it begins through January to July, the analysis of the data, provide an estimate of L∞ of 320mm of length. Through use of the monthly distribution of sizes and the EDKs is observed the presence of two different cohorts during September 89, May 90 and January, the fallowing of the mode value presents of growth on the average total of 21 mm for month. At a level nictímero, the abundance was generally bigger during the day (14:00-18:00), although without showing significant differences. In the habitat CVS, smaller size individuals during the day prevailed, which can be related to feed strategies and evasion of depredators. The abundance of this specie is related to high salinities and low temperatures (bigger abundances to 20°c). For reproductive aspects the values of the gonadosamatic index (IGS) were very low, which explains that the population of this specie, it is constitute by juvenile individuals, in early phases of maturity. Besides it did not observed a well-defined period because they were not found gonads categorized as mature organism, nevertheless, it was proposed to document the periodicity of reproduction according to the months detected as a recruiting periods, according to the before explanation the reproduction of the specie might occur into the fallowing periods from December-January, March- April and July-September.; Con la finalidad de obtener información de la distribución, abundancia, edad crecimiento y reproducción de la lebrancha, Mugil curema, en la Laguna de Pueblo Viejo, Veracruz, se efectuaron muestreos bimestrales, durante un año, con recolectas cada dos horas en 12 ciclos nictímeros, en dos diferentes tipos de hábitat, uno con vegetación sumergida (CVS) y otro sin este tipo de vegetación (SVS).Durante este estudio se capturaron 1,149 individuos. Espacialmente, se capturó un mayor número de individuos en el hábitat CVS (P=0.035). La talla promedio en el hábitat SVS (x =62.68 mm) fue significativamente mayor que en el hábitat CVS (x =50.28), lo cual puede relacionarse con el hecho de que los ambientes con vegetación representan zonas de protección y crianza para individuos juveniles. Analizando el crecimiento de los individuos en ambos hábitat se encontró un intervalo de talla de 19 a 221mm con valores modales entre 22-28mm, 37-50mm y 90 mm siendo poco comunes individuos con tallas mayores a los 160 mm Para el estudio de edad se procesaron otolitos de 85 individuos, las estructuras se prepararon y examinaron por técnicas diferentes pero la evidencia de los anillos no fueron observados claramente. De acuerdo con estas observaciones y tomando en cuenta el análisis de las tallas que presentan los individuos (para ambos hábitat) el 99.8% de los individuos capturados fue menor o igual a los 200mm de longitud patrón (LP), por lo que se puede considerar que la mayoría de los individuos colectados tiene menos de un año de vida. Estacionalmente, la abundancia presentó un pulso importante en el mes de enero (P=0.003), el cual estuvo dominado por individuos pequeños, lo que implica que durante este mes, existe un importante pulso de reclutamiento. y de acuerdo al método que aplica el programa de ELEFAN I, se aprecia dicha cohorte que inicia de enero hasta julio, el análisis de los datos, proporcionó una estimación de L∞ de 320mm. Mediante el uso de la distribución mensual de tallas y los EDKs se observa la presencia de otras dos cohortes en el mes de septiembre 89, mayo 90 además de la de enero, el seguimiento del valor de las modas de estas cohortes presento un ritmo de crecimiento en promedio total de 21 mm por mes. A nivel nictímero, la abundancia generalmente fue mayor durante el día (14:00-18:00), aunque sin mostrar diferencias significativas. En el hábitat CVS, durante el día predominaron individuos de talla menor, lo que podría relacionarse con estrategias de alimentación y de evasión de depredadores. La abundancia de esta especie se relaciona además con altas salinidades y con temperaturas bajas (mayores abundancias a 20°c).Para los aspectos reproductivos los valores del índice gonadosamatico (IGS) fueron muy bajos, lo que explica en gran parte que la población de esta especie, está constituida por individuos juveniles, en fases tempranas de maduración además no se observó un periodo de reproducción bien definido debido a que no se encontraron gónadas categorizadas como maduras, sin embargo se propuso documentar la periodicidad de reproducción acuerdo con los meses que se detectaron como periodos de reclutamiento, respecto a lo anterior la reproducción de la especie podría ocurrir dentro de los periodos de diciembre-enero, marzo-abril y julio-septiembre.